2023
DOI: 10.1007/s10570-023-05091-1
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid dynamics and electrical conductivity under confinement within micro and nanocellulose ionogels

Abstract: To investigate the effect of cellulose matrix on the diffusion and conductivity properties of the ionogels formed with the BMIMCl ionic liquid (IL), two types of samples were made with micro (CMC) and nano (CNC) cellulose. The cellulose interactions with IL were studied by 1H and 13C NMR solid-state spectroscopy. The cation [BMIM]+ self-diffusion coefficient was calculated based on Fast Field Cycling 1H NMR relaxation measurements. The ionic conductivity was measured by the thermal scanning conductometry metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…FFC-NMR relaxometry studies about confined liquid electrolytes have been mostly concentrated on ILs without [103,106,119,121,[142][143][144][145] and with lithium salt [60], and few of them on aqueous electrolyte solutions [146]. Most of them have been focused on the dynamics of the cation ( 1 H NMR) [119,121,142,143,145,146] and only few of them have studied both cation and anion dynamics ( 1 H and 19 F NMR) [60,103,106,108,144].…”
Section: Confined Liquid Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…FFC-NMR relaxometry studies about confined liquid electrolytes have been mostly concentrated on ILs without [103,106,119,121,[142][143][144][145] and with lithium salt [60], and few of them on aqueous electrolyte solutions [146]. Most of them have been focused on the dynamics of the cation ( 1 H NMR) [119,121,142,143,145,146] and only few of them have studied both cation and anion dynamics ( 1 H and 19 F NMR) [60,103,106,108,144].…”
Section: Confined Liquid Electrolytesmentioning
confidence: 99%
“…FFC-NMR relaxometry studies about confined liquid electrolytes have been mostly concentrated on ILs without [103,106,119,121,[142][143][144][145] and with lithium salt [60], and few of them on aqueous electrolyte solutions [146]. Most of them have been focused on the dynamics of the cation ( 1 H NMR) [119,121,142,143,145,146] and only few of them have studied both cation and anion dynamics ( 1 H and 19 F NMR) [60,103,106,108,144]. Many of these works have shown that the confinement causes a slight slowing-down of the ion dynamics, which is consistent with the fact that the ionic conductivity of the confined electrolyte is usually smaller compared to the corresponding value for the pure IL [119].…”
Section: Confined Liquid Electrolytesmentioning
confidence: 99%
“…% was added. Kaszyńska et al [49] and Kowalczuk et al [65] explored how dissolving cellulose at 10 wt. % in [BMIM][Cl] affected the cation dynamics and ionic conductivity.…”
Section: Magnetic Ionic Liquidsmentioning
confidence: 99%
“…Confinement of ILs in polymeric systems has also been explored by FFC NMR relaxometry [34,49,53,[63][64][65]68,69] and some of these studies are mentioned very briefly herein. Neves et al [63] and Martins et al [64] investigated ionic mobility and level of confinement, in addition to the effect of temperature and water content on the molecular structure and dynamics of the IL cations BMIM, DTA (n-dodecyltrimethylammonium) and TMPA (phenyltrimethylammonium) in Nafion membranes.…”
Section: Confined Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation